The Association of Vitamin D Deficiency with Disease Activity in Systemic Lupus Erythematosus: A Systematic Review - Calista Giovani; Charles Sanjaya Seikka (International Medical Journal Corp. Ltd, 2025)
Introduction: Systemic Lupus Erythematosus (SLE) is a complex autoimmune disease characterized by chronic inflammation and multisystem organ damage. Vitamin D, a potent immunomodulator, has been implicated as a potential environmental factor influencing SLE pathogenesis and activity. A high prevalence of hypovitaminosis D is consistently observed in SLE patients, yet its precise role and the therapeutic benefit of supplementation remain areas of active investigation. This systematic review aims to synthesize the current evidence on the association between vitamin D status and disease activity in SLE and to evaluate the efficacy of vitamin D supplementation as an adjunctive therapy. Methods: A systematic search of medical databases was conducted to identify relevant observational studies and randomized controlled trials (RCTs) published up to 2025. Studies were included if they investigated the relationship between serum 25-hydroxyvitamin D levels and SLE disease activity, or the effects of vitamin D supplementation on clinical and serological outcomes in SLE patients. Data on study design, patient characteristics, interventions, and outcomes were extracted. The quality of included RCTs was assessed using the Cochrane Risk of Bias (RoB 2) tool, while observational studies were evaluated using the Newcastle-Ottawa Scale. Results: A total of 17 studies, comprising 12 observational studies and 5 interventional trials, met the inclusion criteria. Observational studies consistently demonstrated a high prevalence of vitamin D deficiency and insufficiency in SLE cohorts. A statistically significant inverse correlation between serum 25(OH)D levels and global disease activity scores (e.g., SLEDAI) was reported in the majority of these studies. Lower vitamin D levels were also associated with specific organ involvement, particularly lupus nephritis, and adverse serological markers, including higher anti-dsDNA titers and lower complement levels. Interventional studies and meta-analyses showed that vitamin D supplementation significantly, albeit modestly, reduced SLEDAI scores. The most consistent clinical benefit was observed in the improvement of patient-reported fatigue. Discussion: The evidence strongly supports a relationship between low vitamin D status and higher disease activity in SLE. The biological plausibility for this association is robust, grounded in vitamin D's multifaceted immunomodulatory effects on both innate and adaptive immunity. While supplementation appears to be a safe and beneficial adjunctive therapy, particularly for managing fatigue, its effect on global disease activity is modest. Heterogeneity in trial designs, including dosing regimens and study duration, contributes to variability in outcomes and highlights the need for larger, standardized trials. Conclusion: Vitamin D deficiency is a significant and modifiable factor associated with increased disease activity in SLE. Routine screening for and correction of hypovitaminosis D is warranted in all SLE patients, both for its established role in bone health and its potential as a low-cost, adjunctive immunomodulatory therapy. Future research should focus on large-scale, long-term RCTs to define optimal dosing strategies and target serum levels for specific clinical phenotypes.